THE USE OF TARSE ART IN THE POETRY OF SHOIRA SHAMS - Gulzoda, Bobonazarova (Journal of Higher Education and Academic Advancement, 2024)
This article deals with the use of verbal arts, mainly tarse art, in the lyric works of Shoira Shams. we paid attention and tried to explain the meaning by means of examples